An ultra‐low cost line follower robot as educational tool for teaching programming and circuit's foundations - Serrano Pérez, Edgar; Juárez López, Fernando (Computer applications in engineering education, 2019)
In this paper, an ultra low‐cost line following robot is presented. The robot is developed through the integration of free educational software and low cost electronics and mechanical devices with the aim of been used as a teaching and learning tool to increase the students confidence/performance and interest in engineering areas. The cost for building this robot‐based educational tool and its related activities is less than 25 USD. Students were encouraged for building its own unique designs using cardboard and open‐source software and hardware. The activities promoted the increase in knowledge and developed student's technical skills such as the use of electronic circuits and sensors, three dimension designs, learning to programming animations and microcontrollers, building self‐made structural and mechanical elements using cardboard and the use of the Bluetooth protocol to achieve the interconnection of devices through the use of an Android based Smartphone. The activities have been developed to allow students to apply and test their own ideas and concepts for solving problems through the computational thinking process and finding digital solutions through programming microcontrollers, all of them in the frame of the maker movement and the inclusion of the arts in the science, technology, engineering and mathematics (STEM) education. The results of confidence/performance and interest evaluation tests allowed to identify the main areas of gain knowledge and the increasing interest in the engineering fields presented in this work.